Pengenalan Strategi Pemasaran pada Produk UMKM Stick Pentol Arsya di Kelurahan Langkap Kabupaten Brebes - Rahman Dani; Mualfin Fahrul Fanani Fanani; Mukhroji Mukhroji (LPPM Universitas Muhadi Setiabudi, 2023)
This dedication aims to analyze and identify marketing strategies that can be applied to introduce Stick Pentol Arsya, a micro, small, and medium enterprises (MSMEs) product, in Langkap Village, Brebes Regency. MSMEs play a significant role in the local economy but often face challenges in marketing their products. The methods used in this study include interviews with the owner of Stick Pentol Arsya MSME, direct observation of the marketing environment, and providing a good and effective understanding of marketing strategies utilizing social media. The research findings indicate that the marketing of Stick Pentol Arsya MSME products can be enhanced through several strategies. Firstly, a strong branding strategy by creating a unique and appealing brand identity to differentiate the product from competitors. Secondly, a promotional strategy through the use of social media and collaboration with local business partners to increase public interest in the product. Furthermore, distribution strategy is also crucial in expanding the product's reach. Stick Pentol Arsya MSME can collaborate with mobile vendors, small shops, and distributors in the Bumiayu sub-district, particularly in the South Brebes region. Additionally, improving product quality and customer service is a key factor in building customer loyalty and satisfaction. In facing market competition, Stick Pentol Arsya MSME needs to continually follow trends and explore new opportunities to develop their product. This dedication provides recommendations for Stick Pentol Arsya MSME to adopt comprehensive marketing strategies and utilize social media to enhance the success of their product marketing in Brebes Regency.